Comparative compressibility of hydrous wadsleyite and ringwoodite: Effect of H2O and implications for detecting water in the transition zone. Issue 12 (23rd December 2015) - Chang, Yun‐Yuan; Jacobsen, Steven D.; Bina, Craig R.; Thomas, Sylvia‐Monique; Smyth, Joseph R.; Frost, Daniel J.; Boffa Ballaran, Tiziana; McCammon, Catherine A.; Hauri, Erik H.; Inoue, Toru; Yurimoto, Hisayoshi; Meng, Yue; et al.
Abstract: Review of recent mineral physics literature shows consistent trends for the influence of Fe and H2 O on the bulk modulus ( K 0 ) of wadsleyite and ringwoodite, the major phases of Earth's mantle transition zone (410–660 km). However, there is little consensus on the first pressure derivative, K 0 ′ = (d K/ d P ) P =0, which ranges from about 4 to >5 across experimental studies and compositions. Here we demonstrate the importance of K 0 ′ in evaluating the bulk sound velocity of the transition zone in terms of water content and provide new constraints on the effect of H2 O on K 0 ′ for wadsleyite and ringwoodite by conducting a comparative compressibility study. In the experiment, multiple crystals of hydrous Fo90 wadsleyite containing 2.0 and 0.25 wt % H2 O were loaded into the same diamond anvil cell, along with hydrous ringwoodite containing 1.4 wt % H2 O. By measuring their pressure‐volume evolution simultaneously up to 32 GPa, we constrain the difference in K 0 ′ independent of the pressure scale, finding that H2 O has no effect on K 0 ′, whereas the effect of H2 O on K 0 is significant. The fitted K 0 ′ values of hydrous wadsleyite (0.25 and 2.0 wt % H2 O) and hydrous ringwoodite (1.4 wt % H2 O) examined in this study were found to be identical within uncertainty, with K 0 ′ ~3.7(2). New secondary‐ion mass spectrometry measurements of the H2 O content of these and previously investigated wadsleyite samples shows the bulk modulus of wadsleyite is reduced by 7.0(5) GPa/wt % H2 O, independent of Fe content for upper mantle compositions. Because K 0 ′ is unaffected by H2 O, the reduction of bulk sound velocity in very hydrous regions of transition zone is expected to be on the order of 1.6%, which is potentially detectible in high‐resolution, regional seismology studies. Key Points: Hydration reduces K 0 of wadsleyite significantly Hydration does not influence d K/ d P of wadslyeite Hydration reduces bulk sound velocity at transition zone conditions